PENDEKATAN INTERDISIPLINER DALAM PENDIDIKAN ISLAM: MENGGABUNGKAN ILMU PENGETAHUAN MODERN DAN NILAI-NILAI KEISLAMAN - Zaenal Mukarom; Yus Hermansyah; Mulkan Karim; Sudrajat, Cucu Jajat; Tondi Nasution (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
The interdisciplinary approach in Islamic education offers a new way of integrating modern science with Islamic values. This research explores how the synergy between contemporary science and Islamic principles can inform a more holistic and relevant educational curriculum. Using qualitative analysis methods, this study identifies practical strategies to combine the two fields effectively. The results of the study show that the interdisciplinary approach not only enriches academic understanding, but also strengthens the moral and ethical foundations in education. This research is expected to provide new insights for educators and policymakers in designing educational programs that balance the needs of modern knowledge with authentic Islamic teachings.